2017
DOI: 10.1186/s12875-017-0581-9
|View full text |Cite
|
Sign up to set email alerts
|

Practice variation in surgical procedures and IUD-insertions among general practitioners in Norway – a longitudinal study

Abstract: BackgroundStudies of Primary Health Care (PHC) reveal considerable practice variations in terms of the range of services provided. In Norway, general practitioners (GPs) are traditionally expected to perform IUD-insertions and several surgical procedures as a part of comprehensive PHC. We aimed to investigate variation in the provision of surgical procedures and IUD-insertions across GPs and over time and explore determinants of such variation.MethodsRetrospective registry study of Norwegian GPs. From a compre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…Although long-acting reversible contraceptives are safe and effective and IUDs are important to women’s sexual health [9], nearly one fifth of the GPs in our study did not insert IUDs. This is in accordance with Pahle et al’s registry study; only three out of four GPs in Norway were reimbursed in 2013 for insertion of IUDs [10]. The same study found considerable practice variation in IUD-insertions depending on the GPs gender, with female GPs having higher odds for performing IUD-insertions (OR 6.28, 95% CI 4.70–8.82) than male GPs.…”
Section: Discussionsupporting
confidence: 87%
“…Although long-acting reversible contraceptives are safe and effective and IUDs are important to women’s sexual health [9], nearly one fifth of the GPs in our study did not insert IUDs. This is in accordance with Pahle et al’s registry study; only three out of four GPs in Norway were reimbursed in 2013 for insertion of IUDs [10]. The same study found considerable practice variation in IUD-insertions depending on the GPs gender, with female GPs having higher odds for performing IUD-insertions (OR 6.28, 95% CI 4.70–8.82) than male GPs.…”
Section: Discussionsupporting
confidence: 87%
“…If women in our study actually were referred to specialized health care for routine testing within The Norwegian Cervical Cancer Screening Programme, our results demonstrate overuse of specialist health care services as cervical screening is supposed to be a primary care undertaking. This reflects a recently observed shift from primary to specialized health care for insertion of intrauterine contraception [ 20 ]. The finding of high numbers of colposcopy, ultrasound, and “complete examinations” in cervical screening appointments adds to this overuse.…”
Section: Discussionmentioning
confidence: 99%